Compact reaction-module on a pad for scalable flow-production of organophosphates as drug scaffolds. Issue 5 (30th January 2020) - Yim, Se Jun; Ramanjaneyulu, Bandaru T.; Vidyacharan, Shinde; Yang, Yu Dong; Kang, In Seok; Kim, Dong-Pyo
Abstract : Continuous pharmaceutical manufacturing receives intense attention as an alternative way to meet flexible market needs with the assurance of higher safety and quality control. Abstract : Continuous pharmaceutical manufacturing receives intense attention as an alternative way to meet flexible market needs with the assurance of higher safety and quality control. Here, we report a compact reaction-module on a pad (CRP, 170 × 170 × 1.2 mm) for scale-up production of drug precursors in a continuous-flow. The CRP system was devised by stacking 9 films of the patterned polyimide to integrate micro-flow circuits, combining the functions of the even distribution of feeds, being completely mixed in less than a few milliseconds. A methodology of using a highly reactive species for the single-step synthesis of α-phosphonyloxy ketone, a drug scaffold, required the synthesis time of a few seconds in microfluidics. The fast reaction in the single CRP was capable of producing 19.2 g h −1 drug precursor, which indicates a solid step toward kilogram-scale pharmaceutical manufacturing in small footage.